ChemInform Abstract: Enantioselective Organocatalytic Partial Transfer Hydrogenation of Lactone‐Fused Quinolines. Issue 48 (2nd December 2014) - Aillerie, Alexandre; Lemau de Talance, Vincent; Moncomble, Aurelien; Bousquet, Till; Pelinski, Lydie
Abstract A first organocatalytic transfer hydrogenation of lactone‐fused quinolines to synthesize a range of aza‐podophyllotoxin derivatives (II) is developed.